Wastewater biofilm formation on self-assembled monolayer surfaces using elastomeric flow cells. (June 2019) - Siddique, Arslan; Suraraksa, Benjaphon; Horprathum, Mati; Oaew, Sukunya; Cheunkar, Sarawut
Abstract: In anaerobic wastewater treatment, microbial biofilm is beneficial for efficient substrate utilization and for preventing the wash-out of key microorganisms. By providing solid supports, biofilm formation can be accelerated due to the early initial adhesion of residing microbes. Alteration in surface properties is therefore one such approach that helps us understand microbial interfacial interaction. Here, self-assembled monolayers of alkanethiols with carboxyl (-COOH), hydroxyl (-OH), and amine (-NH2 ) terminal moieties on gold (Au) substrates were employed to study the initial adhesion of wastewater microbes. An elastomeric flow cell was also utilized to simulate the environment of wastewater bioreactor. Results from fluorescence in situ hybridization (FISH) portrayed more enhanced microbial adhesion after 2 h on -NH2 functional group with the calculated surface coverage of 12.8 ± 2.4% as compared to 7.7 ± 1.6% on -COOH, 11.0 ± 2.0% on -OH, and 1.2% on unmodified Au surfaces. This might be because of concomitant electrostatic attraction between negatively-charged bacteria and positively-charged (-NH3 + ) functional groups. Nevertheless, the average surface coverage by individual biofilm clusters was 28.0 ± 5.0 μm 2 and 32.0 ± 9.0 μm 2 on -NH2 and -OH surfaces, respectively, while -COOH surfaces resulted in higher value (60.0 ± 5.0 μm 2 ) and no significant cluster formation was observed on Au surfaces. Accordingly, the average inter-cluster distance observed on -NH2 surfaces was relatively smaller (3.0 ± 0.6 μm) as compared to that on other surfaces. Overall, these data suggest favorable initial biofilm growth on more hydrophilic and positively-charged surfaces. Furthermore, the analysis of the mean fluorescence intensity revealed preferred initial adhesion of key microbes (archaea) on -OH and -NH2 surfaces. Indeed, results obtained from this study would be beneficial in designing selective biointerfaces for certain biofilm carriers in a typical wastewater bioreactor. Importantly, our elastomeric flow cell integrated with SAM-modified surfaces demonstrated an ideal platform for high-throughput investigation of wastewater biofilm under controlled environments. Graphical abstract: Image 1 Highlights: An elastomeric flow cell for the investigation of wastewater biofilm considering initial adhesion and progression phase Au-coated slides were employed for the assembly of functional groups to examine microbial biofilm formation. Surfaces with -NH2 and -OH functional groups showed enhanced microbial adhesion and initial biofilm formation. Cluster coverage was lower on -NH2 and archaeal adhesion displays favorable on more hydrophilic and positively-charged surface.